2019
DOI: 10.1021/acsanm.9b01464
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Voltmeter Using Colloidal Fe3O4@SiO2 Nanoparticles as an Overpotential Alarm System for Zinc–Air Batteries

Abstract: In rechargeable batteries, overpotential problems may occur especially when the battery is aging. An alarm system to prevent overpotential may be useful. Colloidal nanoparticles of Fe3O4@SiO2 can self-assemble into amorphous photonic crystals (APCs) with tunable interparticle distances as a function of applied voltage. Here, we fabricated a colloidal APC that changes its color from mahogany to dark blue at applied voltages from 1.0 to 4.0 V, respectively. Citrate-modified Fe3O4 was solvothermally synthesized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…APCs can be embedded in or constructed by responsive materials with optical signals modulated in response to external stimuli, including mechanical deformation, 29,180 temperature, 30,166,170 light, 24,75 humidity, 21, 23 magnetic 28,82 and electric fields. 19,41 In addition, the combination of non-iridescent properties of APCs and iridescent structural colors of PCs provides new ideas for anti-counterfeit labels. 51, 178…”
Section: Applications Of Apcsmentioning
confidence: 99%
See 2 more Smart Citations
“…APCs can be embedded in or constructed by responsive materials with optical signals modulated in response to external stimuli, including mechanical deformation, 29,180 temperature, 30,166,170 light, 24,75 humidity, 21, 23 magnetic 28,82 and electric fields. 19,41 In addition, the combination of non-iridescent properties of APCs and iridescent structural colors of PCs provides new ideas for anti-counterfeit labels. 51, 178…”
Section: Applications Of Apcsmentioning
confidence: 99%
“…Their orientations could be changed by a magnetic field, and the structural color changed accordingly. 28 To construct the electrically responsive APCs sensor, 41 Chung et al reported the APCs self-assembled by Fe 3 O 4 @SiO 2 , whose structural color changed from mahogany to dark blue under the voltage ranging from 1.0 to 4.0 V. 19 Recently, Ge et al reported for the first time that a thin layer chromatography (TLC) based on mesoporous silica particle was assembled with high separation efficiency and convenient recognition (Fig. 10f and g).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface treatment with silane coupling agents showed some improvement on the magnetization efficiency of magnetic elastomers. [ 43 ] In magnetic hydrogels, a core–shell approach, specifically covering Fe 3 O 4 cores with SiO 2 shells by Stöber's method, [ 44,45 ] was shown to be effective in achieving nearly individual particle‐level dispersion when coupled with the negative charging of the particle surface in acidic environments. [ 46 ] Finally, the core–shell structure of neodymium iron boron (NdFeB) covered by silver has merit in obtaining both strong ferromagnetic properties and high electrical conductivity.…”
Section: Materials: Classification and Fabricationmentioning
confidence: 99%
“…It has been discussed that the high surface charge of the nanospheres has great contribution to the stability of slurry, which is important in the regulation of structural color under the electric field. Subsequently, nanospheres of various materials have been widely used as the basic units for constructing electrophoretic ERPC with an opal structure, such as ZnS@SiO 2 , SiO 2 @TiO 2 , Fe 3 O 4 @C, , Fe 3 O 4 @SiO 2 , TiO 2 , SiO 2 , and CeO 2 @SiO 2 . In addition, a polyelectrolyte gel with an inverse opal structure has also been used to fabricate typical electrophoretic ECPC devices …”
Section: Introductionmentioning
confidence: 99%